The Relationship between Natural Environment Relatedness and Emotional Well-Being: A Systematic Review and Proposed Conceptual Framework Experience - Ahmad, Noorlila; Abd Rahman, Siti Fatimah (IIUM Journal of Educational Studies, 2021)
The influence of the natural environment on emotional well-being has been highlighted at the peak of the Covid 19 pandemic that saw most countries impose prolonged total lockdowns and movement restrictions on their citizens. While researchers have recently emphasized the need to focus not only on students’ academic achievement but also on their inner needs, which include their emotional well-being, studies have found nature connectedness has a positive effect on emotional well-being and physical health. Many studies on nature and well-being have focused on physiological and psychological experimental research to examine before and after exposure to nature. However, there is still a need for further investigation how emotional connection between nature environments in the aspect of restorativeness and spiritual values improve mental health. This paper systematically reviewed previous studies about the relationship between exposure to the natural environment and well-being focusing on key variables, underpinning theories, methodological processes and samples. As a result of the review, a conceptual framework is proposed for future studies on relationship between exposure to the natural environment and well-being. We hope that the proposed framework will be empirically tested in future studies.